Pengaruh Model Pembelajaran Predict-Observe-Explain terhadap Kemampuan Berpikir Kreatif - Laila Bahroini; Ummi Shofia Agustin (Universitas Indraprasta PGRI, 2017)
This research examined the influence of Predict-Observe-Explain learning model on the ability of students’ creative thiking in the material of building the flat side room subject of 2nd grade of Islamic Junior High Shcool Sunan Gunung Jati. This research used a quantitative approach, and the research design used randomized subject design posttest only control group design that is random controlling by performing the test at the end of treatment. The test used to test the hypotesis was kolmogorov semirnov test. The purpose of this research was to know the influence of students’ creative thiking using Predict-Observe-Explain learning model on students’ creative thiking ability in the material of building the flat side room at Islamic Junior High School Sunan Gunung Jati.